Pengembangan Media Pembelajaran Interaktif Untuk Meningkatkan Minat Belajar Pada Mata Pelajaran Informatika di Kelas X SMK - Anyan, Anyan; Edy Setyawan, Antonius (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
The background of this research is the process of using interactive learning media which is still less creative so that students find it difficult to receive learning material, which results in reduced student interest in learning. This research aims to evaluate the effectiveness of interactive learning media in increasing students' interest in learning, with a focus on aspects of active participation and student involvement in the learning process.  The research method used is development research (R&D) with the ADDIE development model (Analysis, design, development, implementation, evaluation) with procedures: analysis stage, design stage, development stage, implementation stage and evaluation stage. Data collection tools include test questions, questionnaires, observation sheets and documentation. The validation results from media experts obtained a result of 82% in the very feasible category, and the assessment from material experts was 100% in the very feasible category. and pre-test results of 60.5% show good understanding of the material. The results of students' learning interest increasing significantly can be seen from the results pretest in small-scale trials an average of 60.5% indicates the need to improve overall student understanding, and posttest 85.5% in the very good category, and wide-scale trials obtained average results pretest 67.2% indicated the need to improve overall student understanding and outcomes posttest 88.67% in the very good category.  the effectiveness of interactive learning media in increasing students' interest in learning in getting calculated grades effect size namely 1.30 in the "Very High" category. The implications of this research can encourage the development of educational policies that support the integration of technology in learning in secondary schools. By considering the positive results from the use of interactive media, educational policies can promote the development of students' digital competence and increase accessibility to technology in the learning process.